MODIFICATION OF HUMIC SUBSTANCES FOR DEVELOPMENT OF MATERIALS FOR ENVIRONMENTAL TECHNOLOGIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Humic substances are high molecular weight refractory polycationites formed during decay of living organic matter and through biosynthesis of low molecular weight organic substances (metabolites or decay products of living organisms). Presence of many functional groups in the structure of humic substances determines their ability to interact with metal ions forming stable complexes and influencing metal ion speciation in the environment and mobility, behaviour and speciation forms in the environment. Presently humic substances are a product of industrial scale and quantities in amounts of hundreds of tons are produced. The aim of this study is to analyse derivatization possibilities of humic substances. To achieve this aim derivatization of humic substances using acylation (at first introduction of acetylgroups, but also changing length acyl chains are considered) are used. Also alkylation is used. Mild oxidation can help to obtain modified products with reduced molecular weight. Another approach includes introduction of new functional groups and structures. To achieve this aim, conjugates with short peptides, amines and sugar derivatives using coupling with water-soluble carbodiimides are obtained. As basic characteristics elemental analysis as well as functional analysis have been used, supported with Fourier transform infrared (FTIR), 13C nuclear magnetic resonance spectrometry and other methods. Derivatives of humic substances containing sulpho, amino, and hydroxylgroups and thiolgroups were synthesized and their properties were analyzed in respect to their their elemental composition; functional group content changes in spectral characteristics. The derivatives of humic substances showed significant differences in the number and in ability to interact with the metal ions, which were reflected in their complexation properties towards metal ions. FTIR spectra gave evidence of the presence of metal ions, strongly bound and protected in inner sphere complexes. The obtained derivatives of humic substances can be used for remediation of environment contaminated with heavy metal ions.